A Facile Low-Temperature Hydrothermal Method to Prepare Anatase Titania/Cellulose Aerogels with Strong Photocatalytic Activities for Rhodamine B and Methyl Orange Degradations. (4th May 2015) - Wan, Caichao; Lu, Yun; Jin, Chunde; Sun, Qingfeng; Li, Jian
Abstract : A facile low-temperature hydrothermal method for in situ preparation of anatase titania (TiO2 ) homogeneously dispersed in cellulose aerogels substrates was described. The formed anatase TiO2 aggregations composed of a mass of evenly dispersed TiO2 nanoparticles with sizes of 2−5 nm were embedded in the interconnected three-dimensional (3D) architecture of the cellulose aerogels matrixes without large-scale reunion phenomenon; meanwhile, the obtained anatase titania/cellulose (ATC) aerogels also had a high loading amount of TiO2 (ca. 35.7%). Furthermore, compared with commercially available Degussa P25, ATC aerogels displayed comparable photocatalytic activities for Rhodamine B and methyl orange degradations under UV radiation, which might be useful in the fields of catalysts, wastewater treatment, and organic pollutant degradation. Meanwhile, the photocatalytic reaction behaviors of ATC aerogels under UV irradiation were also illuminated.